Effect of Genotype and Age on Egg Quality Traits in Naked Neck Chicken under Tropical Climate from India - Rajkumar, U.; Sharma, R.P.; Rajaravindra, K.S.; Niranjan, M.; Reddy, B.L.N.; Bhattacharya, T.K.; Chatterjee, R.N. (International Journal of Poultry Science, 2009)
A comprehensive study was undertaken to evaluate the egg quality traits in three naked neck genotypes, NaNa (homozygous), Nana (heterozygous) and nana (normal) by utilizing 556 eggs collected at 28, 32, 36 and 40 weeks of age. The overall mean egg weight, shape index and Haugh unit values were 56.41 g, 75.79 and 75.98, respectively. The yolk index, yolk height and yolk colour varied significantly (p<0.01) in three genotypes. All other external and internal egg quality traits were not differed significantly among the genotypes; however Naked neck had better egg quality in almost all the traits. Age had significant (p<0.01) effect on all the traits studied in Naked neck chicken. Haugh unit score was better in 28 week age group. The egg, yolk, albumin and shell weights were positively correlated with the age. The average shell weight and thickness values were 5.07 g and 0.401 mm, respectively, which had no significant variation among the genotypes. The Na gene had marginal effect on all the egg quality traits studied. The better egg quality parameters in naked neck chicken are desirable which indicate the better keeping quality of the eggs and withstand the handling damages.